The role of municipalities in energy governance in South Africa - Mosdell, Susan Carolyn (Department of Public Law, 2016)
It is commonly known and acknowledged in contemporary times that the burning of coal and other fossil fuels has caused environmental harm on a global scale, especially global warming caused by emissions of carbon dioxide and other gases. Nuclear energy does not cause emissions, but the risk of nuclear accidents is a deadly and serious one for communities close to nuclear power stations.8 Furthermore, humans have not yet found a completely safe method for disposal of nuclear waste.9 Florini and Sovacool write that global energy governance is currently on an unsustainable and conflict-prone path. There are issues of unreliable supply, brittle and vulnerable energy infrastructure, massive environmental degradation, and failure to deliver energy services.10 Udall goes so far as to say that 'energy is the original currency', and that mankind is at the beginning of a period of resource nationalism.11 Victor and Yueh endorse this view, saying that the decade between 2000 and 2010 has seen governments in all the large consumer nations of the world besieged by doubts about their energy security.12 The increasing demand for energy across the world has a number of consequences. Among these, the most challenging for governments is the association of energy generation with climate change, resulting from emission of greenhouse gases in the process of burning fossil-based fuels to generate electricity.13 Victor and Yueh describe the energy sector as one of the most exciting technological frontiers in the world, with many countries changing their expectation as to what the sector should deliver, due to climate change.14 Across the world, renewable energy sources are being recognised as the safest and most desirable energy sources, as they are largely free of emissions and are non-depletable.15 In South Africa the legislative framework explicitly promotes the development and use of renewable energy. In this dissertation it will be shown how municipalities in South Africa can play a valuable role in energy governance, which, it is posited, is a central element of their legislative responsibilities with regard to service delivery, upholding of the Bill of Rights, promoting a safe and healthy environment, promoting local economic development, and other issues.